Slicer Endonuclease Argonaute 2 Is a Negative Regulator of Hematopoietic Stem Cell Quiescence. (28th March 2016) - Lu, Kenneth; Nakagawa, Masahiro Marshall; Thummar, Keyur; Rathinam, Chozha Vendan
Abstract: Hematopoietic stem cells (HSCs) are capable of both self-renewing throughout the lifetime of an organism and differentiating into all lineages of the blood system. A proper balance between quiescence and proliferation is critical for the self-renewal and functions of HSCs. The choice of HSCs to remain quiescent or to enter proliferation has been tightly regulated by a variety of cell intrinsic and extrinsic pathways. Identifying molecular players that control HSC quiescence and proliferation may lead to new treatment strategies and therapeutic interventions for hematologic disorders. To identify the functions of the slicer endonuclease Argonaute (Ago) 2 in the physiology of HSCs, we generated Ago2 Hem-KO mice, that are deficient for Ago2 in HSCs and in their progeny. Analysis of Ago2 Hem-KO mice indicated that a loss of Ago2 results in reduced HSC pool size and altered frequencies of hematopoietic progenitors. Ago2 deficient HSCs exhibit defective multilineage differentiation capacities and diminished repopulation abilities, in a cell intrinsic manner. Interestingly, Ago2 mutant HSCs remain largely quiescent and show reduced entry into cell cycle. Genome-wide transcriptome studies and gene set enrichment analysis revealed that Ago2 deficient HSCs downregulate the "HSC signature" and upregulate the "lineage signature." Moreover, our analysis on transcription factors (TFs) identified that a loss of Ago2 is sufficient to alter the "molecular signature" and "TF networks" that control the quiescent and proliferative states of HSCs. In essence, our study identified Ago2 as a key determinant of quiescence exit in HSCs. Abstract : A deficiency of the slicer endonuclease Argonaute (Ago) 2, a key enzyme involved in the miRNA biogenesis pathway, in HSCs causes defective self-renewal, reduced proliferation and augmented myeloid differentiation due to alterations in the molecular signature and Transcription Factor networks.